Speaker Identification by Specrograms - J, Latha (Journal of All India Institute of Speech and Hearing)
The present study was aimed to find out the possibilities of speaker identification by verifying the spectrograms, based on acoustic features and to identify the acoustic fea ures necessary for verifying the speaker, by comparing the spectrograms.